2015
DOI: 10.1002/ejp.716
|View full text |Cite
|
Sign up to set email alerts
|

A novel electroencephalography‐based tool for objective assessment of network dynamics activated by nociceptive stimuli

Abstract: Background: Pain perception is typically assessed using subjective measures; an objective measure of the response to pain would be valuable. In this study, Brain Network Activation (BNA), a novel multivariate pattern analysis and scoring algorithm, was applied to event-related potentials (ERPs) elicited by cortical responses to brief heat stimuli. Objectives of this study were to evaluate the utility of BNA as a quantitative and qualitative measure of cortical response to pain. Methods: Contact Heat Evoked Pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…The RBNM was characterized with central theta-delta activations and represented the response to pain of healthy individuals (Fig 4, top left). This network has been validated in a previous study 36 in which we showed a similar central theta-delta network for CHEPs at 52°C. The dynamics of the network activity can be revealed in a frame-by-frame presentation (Fig 4, bottom), with a heat probe applied, activating pain-related network activity (Fig 4, top right).…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…The RBNM was characterized with central theta-delta activations and represented the response to pain of healthy individuals (Fig 4, top left). This network has been validated in a previous study 36 in which we showed a similar central theta-delta network for CHEPs at 52°C. The dynamics of the network activity can be revealed in a frame-by-frame presentation (Fig 4, bottom), with a heat probe applied, activating pain-related network activity (Fig 4, top right).…”
Section: Methodssupporting
confidence: 83%
“…In addition, we assessed biomarkers of response, including an electroencephalography (EEG)/ event-related potential (ERP) analysis of brain reorganization, known as brain network activation (BNA). 33,36,39 The exploratory aims were to test screening procedures to predict response and individualize treatment.…”
mentioning
confidence: 99%
“…According to the guidelines issued by the International Federation of Clinical Neurophysiology, and the Neuropathic Pain Special Interest Group of the IASP, laser evoked potentials (LEPs) related to Aδ‐fibre activation are the easiest and most reliable neurophysiological technique for assessing nociceptive system function (Cruccu et al., ; Haanpää et al., ). Among nociceptive evoked potentials, contact‐heat‐evoked potentials (CHEPs) are also commonly used for investigation of patients with neuropathic pain, and several studies have indicated that CHEPs are mediated by Aδ‐fibre activation (Granovsky et al., ; Reches et al., ). Pain related evoked potentials by concentric electrode stimulation (PREPs) have also been introduced to assess nociceptive system.…”
Section: Introductionmentioning
confidence: 99%
“…A recent approach that examines ERPs via a brain network activation (BNA) analysis may provide the next step in the evolution of EEG as an accepted tool for diagnosis and recovery assessment. A detailed description of the BNA algorithm is provided elsewhere ( 23 27 ); thus, only a brief summary of the method is given here. BNA analysis is a new tool for evaluating the network dynamics associated with brain responses (i.e., ERPs).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the BNA algorithm extracts the interparticipant sequential temporal co-occurrence of pairs of ERP peaks (event pairs) extracted from signals that were band-pass filtered into different frequency ranges and that emerged in different spatial locations. Next, BNA integrates group-common event pairs of specific temporal relations, spatial locations frequencies, and amplitudes into a unified functional network, which is the BNA group network ( 25 27 ). This stage must be completed only once as it becomes the normative group for comparison for future clinical comparisons.…”
Section: Introductionmentioning
confidence: 99%